Promising Bioactivity of Vitamin B1-Au Nanocluster: Structure, Enhanced Antioxidant Behavior, and Serum Protein Interaction - Ditta Ungor; Gyöngyi Gombár; Ádám Juhász; Gergely F. Samu; Edit Csapó (MDPI AG, 2023)
In the current work, we first present a simple synthesis method for the preparation of novel Vitamin-B1-stabilized few-atomic gold nanoclusters with few atomic layers. The formed nanostructure contains ca. eight Au atoms and shows intensive blue emissions at 450 nm. The absolute quantum yield is 3%. The average lifetime is in the nanosecond range and three main components are separated and assigned to the metal-metal and ligand-metal charge transfers. Based on the structural characterization, the formed clusters contain Au in zero oxidation state, and Vitamin B1 stabilizes the metal cores via the coordination of pyrimidine-N. The antioxidant property of the Au nanoclusters is more prominent than that of the pure Vitamin B1, which is confirmed by two different colorimetric assays. For the investigation into their potential bioactivity, interactions with bovine serum albumin were carried out and quantified. The determined stoichiometry indicates a self-catalyzed binding, which is almost the same value based on the fluorometric and calorimetric measurements. The calculated thermodynamic parameters verify the spontaneous bond of the clusters along the protein chain by hydrogen bonds and electrostatic interactions.